Model Perumusan Kebijakan “Public Mechanism Approach” Perencanaan Pembangunan Daerah di Kabupaten Gorontalo - Rustam Tohopi; Yakob Noho Nani; Yanti Aneta (Program Studi Administrasi Negara Universitas Serang Raya, 2021)
AbstractObjectives - This research is conducted to describe the stages and mechanisms of development planning policy formulation. The stages and mechanisms of planning will be examined in more depth about the process of public involvement in every approach used in the implementation of the development planning system. The collection of research data was conducted through an in-depth interview process of 30 informants at the Gorontalo District Regional Development Planning Agency. Findings - Based on the results of the study, increased effectiveness of Regional Development planning through the Public Participation Approach or through the Approach Mechanism (PM-A) Original – The Public Mechanization Approach Emphasizes the importance of the stages of Public Testing in policy formulation. This stage is done for the achievement of policy objectives in accordance with the targets appropriately.